Does specialty training prepare doctors for senior roles? A questionnaire study of new UK consultants. Issue 1044 (5th July 2012) - Morrow, Gill; Burford, Bryan; Redfern, Nancy; Briel, Ruth; Illing, Jan
Abstract : Aim: To measure new consultants' perceptions of their preparedness for different clinical and non-clinical aspects of the role of consultant. Design: A cross-specialty questionnaire was developed and validated, containing items asking how well specialty training had prepared respondents for the role of consultant in a number of clinical and non-clinical areas. Responses were on a five-point Likert scale with a 'Not relevant/no opinion' box, and one free text section. Analysis was carried out on 10 scales derived from the questionnaire items through exploratory factor analysis. Participants: Consultants who had completed their specialty training in the north of England between 2004 and 2009 and had held a substantive consultant post in the region for <5 years were sent questionnaires in late 2009. Results: The effective response rate was 70.6% (211/299). Ten factors reflecting areas including clinical skills, communication skills, team and resource management were identified. Overall, higher scores were observed on factors relating to 'providing care for individual patients' rather than 'having responsibility for the system of care'. The lowest scoring factors related to resource management and supervision, with mean scores falling below the scale midpoint. There were no significant differences between specialty groups, or on any demographic variables. Conclusions: A questionnaire to measure new consultants' perceptions of how well their specialty training had prepared them for practice was developed and validated. Findings were similar across specialties, suggesting that training programmes in all areas need to integrate higher-level management skills into their curricula, alongside the development of clinical expertise.